2017
DOI: 10.1152/ajpgi.00441.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the use of statins in liver disease

Abstract: The evolution of chronic liver injuries from benign and manageable dysfunction to life threatening end-stage liver disease with severe complications renders chronic liver disease a global health burden. Because of the lack of effective medication, transplantation remains the only and final curative option for end-stage liver disease. Since the demand for organ transplants by far exceeds the supply, other treatment options are urgently required to prevent progression and improve end-stage liver disease. Statins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 55 publications
1
47
0
9
Order By: Relevance
“…Advanced atherosclerotic lesions contain cells with markers of senescence, including senescence-associated β-galactosidase, p16 Ink4a , p53, p21, and shortened telomeres (Minamino and Komuro, 2007). While indirect causation studies in mice originally suggested a pro-atherogenic role of senescent lesional cells, genetic association studies in mice and humans have called into question this conclusion (Schierwagen et al, 2017). However, a more definitive causation study has been recently conducted using Western diet-fed Ldlr -/- mice in which lesional macrophages, VSMCs, and endothelial cells expressing p16 Ink were genetically eliminated (Childs et al, 2016).…”
Section: Aging Affects Immune Cell Function In Atherosclerosismentioning
confidence: 99%
“…Advanced atherosclerotic lesions contain cells with markers of senescence, including senescence-associated β-galactosidase, p16 Ink4a , p53, p21, and shortened telomeres (Minamino and Komuro, 2007). While indirect causation studies in mice originally suggested a pro-atherogenic role of senescent lesional cells, genetic association studies in mice and humans have called into question this conclusion (Schierwagen et al, 2017). However, a more definitive causation study has been recently conducted using Western diet-fed Ldlr -/- mice in which lesional macrophages, VSMCs, and endothelial cells expressing p16 Ink were genetically eliminated (Childs et al, 2016).…”
Section: Aging Affects Immune Cell Function In Atherosclerosismentioning
confidence: 99%
“…However, intrahepatic inflammatory stimuli and portal hypertension can persist [13,14]. Larger trials are required to investigate whether patients successfully treated for hepatitis B and hepatitis C infections and those with non-alcoholic steatohepatitis with persistent metabolic damage can profit from adjuvant medications, such as non-selective beta blockers (NSBB) [15], renin-angiotensin system inhibitors [16], statins [17] or rifaximin [18], alone or in combination [19,20]. All these drugs blunt inflammatory stimuli and reduce portal pressure.…”
Section: Blunting Formation Of Varicesmentioning
confidence: 99%
“…In light of current literature, this fear seems unjustified since statin liver toxicity is a rare event [8••]. Moreover, recent data point to potentially beneficial and previously unexpected effects of statins in CLD and cirrhosis [9]. In this review, we summarize current evidence regarding the influence of statins in endothelial dysfunction in CLD, their ability to modulate hepatic fibrogenesis, and their vasoprotective effects in portal hypertension as well as on existing data about the impact of statins in cirrhosis development, progression, and complications.…”
Section: Introductionmentioning
confidence: 99%